Neonatal barbiturate withdrawal. - Blumenthal, I. (BMJ Group, 1977)
An infant with neonatal barbiturate withdrawal syndrome is reported. The clinical features, diagnosis and treatment of this condition are discussed. A retrospective review of fifty-three infants of barbiturate-treated epileptic mothers indicated a high incidence of "jitteriness" (17%) and feeding problems (36%) in the immediate neonatal period.